Truth Be in the Field: Conducting Comparative Survey Research in a Multicultural Society such as South Africa. Issue 2 (3rd March 2020) - Struwig, Jarè; Roberts, Benjamin J.
Abstract: Set against growing interest and advances in relation to multinational, multiregional, and multicultural (3MC) survey research, this paper will reflect on some of the survey challenges that inevitably confront the survey scientist in South Africa. South Africa is a heterogeneous, multicultural society with a variety of socio-economic problems and large inequalities and endeavors to collect data involves appreciable challenges. This paper will use examples and experiences from the South African Social Attitude Survey (SASAS) which has been conducted annually since 2003 in South Africa. It will also reflect on challenges experienced as part of participating in cross-national survey research, specifically focusing on its participation in the International Social Survey Program (ISSP), as well as more recent engagement with the European Social Survey (ESS) and International Wellbeing Group (IWbG). This paper will focus on practical, field-related difficulties that may arise and will discuss how these challenges is best handled within the South African context.